Strategi Pengembangan Ekowisata Melalui Peningkatan Partisipasi Masyarakat di Desa Topejawa Kecamatan Manggarabombang Kabupaten Takalar - Nur Helminah; Haeruddin (Jurnal Berita Sosial, 2023)
This study uses a type of qualitative research with a sociological approach which is located at the Topejawa beach tourist attraction, Topejawa Village, Mangarabombang District, Takalar Regency. The sources of data used in this study are primary data and secondary data. Data collection techniques are carried out through observation, interviews, documentation. Data analysis was carried out by data reduction, data presentation and then drawing conclusions. The results of this study indicate that community participation plays a very important role in developing ecotourism on the coast of Tojawa. Starting from the proposal of policies and expectations from the community to increase their economic income is a gift for some people who can work in these tourist attractions, community participation in the field of facilities and infrastructure is very influential. The community as labor is the spearhead of a job, especially for this tourist attraction which requires quite a lot of energy and hard work in it.